Microwave engineering : concepts and fundamentals - Khan, Ahmad Shahid (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
"This book presents comprehensive material on microwave engineering. Though there are a number of books on this subject but none of them covers all the aspects in detail and with the equal emphasis. In the present text almost all topics including microwave generation, transmission, measurement and processing are given almost the equal weightage"--
Preface Introduction Microwave Frequency Bands Advantages Components of Microwave System Applications Health Hazards Fundamentals of Wave Propagation Basic Equations and Parameters Nature of Media Wave in Lossless Media Wave in Lossy Media Conductors and Dielectrics Polarisation Depth of Penetration Surface Impedance Poynting Theorem Reflection and Refraction Direction Cosines, Wavelength and Phase Velocity Classification of the Cases of Reflection Normal Incidence Cases Oblique Incidence Parallel Plane Guide Transverse Waves Characteristics of TE and TM Waves Transverse Electromagnetic Waves Wave Impedances Attenuation in the Walls of Parallel Plane Guide Transmission Lines Equations Governing Transmission Line Behaviour Lossless RF and UHF Lines with Different Terminations Reflection Phenomena Resonance Phenomena in Line Sections Quality Factor of a Resonant Section UHF Lines as Circuit Elements Applications of Transmission Lines Types of Transmission Lines Coaxial Cables Limitations of Different Guiding Structures Waveguides Interrelation between Transmission Line and Waveguide Rectangular Waveguide Circular Waveguide Dielectric Waveguides Physical Interpretation of Wave Terminology Relative Merits of Waveguides Limitations of Waveguides Cavity Resonators Shapes and Types of Cavities Cavity Formation Fields in Cavity Resonators Quality Factor Coupling Mechanism Tuning Methods Advantages and Applications Dielectric Resonators Microwave Ferrite Devices Ferrites Faraday's Rotation Non-Reciprocal Ferrite Devices Ferrite Phase Shifter Ferrite Attenuators Ferrite Switches YIG Filters Figures of Merit of Ferrite Devices Smith Chart Characteristic Parameters of a Uniform Transmission Line Polar Chart Smith Chart for Impedance Mapping Smith Chart for Admittance Mapping Information Imparted by Smith Chart Advantages of Smith Chart Smith Chart for Lossless Transmission Lines Stub Matching Components Microwave Components Waveguides and Its Accessories Input-Output Methods in Waveguides Coaxial to Waveguide Adapter Waveguide Junctions Directional Couplers Waveguide Terminations Attenuators Impedance Matching Tuners Phase Shifters Microwave Filters Duplexers Diplexers Mode Suppressors Scattering Parameters Properties of Scattering Matrices Scattering Parameters for Networks with Different Ports Nature of Networks Types of s-Parameters Scattering Matrices for Some Commonly Used Microwave Components Electrical Properties of 2-Port Networks s-Parameters and Smith Chart Scattering Transfer (or T) Parameters Microwave Antennas Antenna Theorems and Characteristic Parameters Types of Microwave Antennas Antenna Arrays Microstrip Antennas Microwave Measurements Klystron Power Supply VSWR Meter Travelling Wave Detection Qualities of Microwave Components and Devices Precautions Some Standard Norms Measurement of Basic Quantities Some Practical Applications Basics of Microwave Tubes Frequency Limitations of Conventional Tubes Influence of Fields on Motion of Charged Particles Velocity Modulation Classification of Microwave Tubes Microwave Tubes Klystron Two-Cavity Klystron Reflex Klystron Travelling-Wave Tube Magnetron Crossed-Field Amplifier Backward-Wave Oscillators Microwave Diodes Basics of Semiconductor Devices Conventional Diodes Microwave Diodes Transferred Electron Devices Avalanche Transit Time Devices Parametric Devices Masers Microwave Transistors Transistors and Vacuum Tubes Microwave Transistors Field Effect Transistors Metal-Oxide-Semiconductor Transistors Memory Devices Charge-Coupled Devices Planar Transmission Lines Striplines Microstrips Coplanar Waveguides Coplanar Strips Slot Line Fin Lines Micromachined Lines Realisation of Lumped Elements Realisation of Microwave Components Microwave Integrated Circuits Merits and Limitations of MICs Types of MICs Materials Used Fabrication Techniques Fabrication Processes Illustration of Fabrication by Photo-Resist Technique Fabrication of Devices Appendices Index
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Microwaves; Microwave devices; TECHNOLOGY & ENGINEERING / Lasers & Photonics; TECHNOLOGY & ENGINEERING / Material Science; TECHNOLOGY & ENGINEERING / Microwaves